ANALISIS PENGARUH PENGETAHUAN INVESTASI, PERSEPSI RISIKO, MOTIVASI INVESTASI, DAN MODAL INVESTASI TERHADAP MINAT INVESTASI DI PASAR MODAL PADA MAHASISWA UNPRI - Graciela Wijaya; Sherly Winata; Adinda Megawati Pardosi; Mesrawati Mesrawati; Arridho Abduh (ITB AAS Indonesia Surakarta, 2024)
In the past few years, the number of young investors has continued to grow, but not the quality. Therefore, the authors, as an UNPRI student, wanted to conduct research related to this matter. The purposes of this research is to test and analyze the influence of investment knowledge, risk perception, investment motivation, and investment capital and investment interest in capital market among UNPRI students partially and simultaneously. This research used a saturated sample method with a total sample of 125 respondents, who were students from the law faculty, psychology faculty, and science and technology faculty at UNPRI. The analysis technique uses multiple linear regression analysis and the data is processed using the program SPSS 23.0 version. Based on the research, it was found that (1) the investment knowledge variable partially had no effect on investment interest, (2) the risk perception variable partially had no effect on investment interest, (3) the investment motivation variable partially had an effect on investment interest, and (4) the variable Investment capital partially influences investment interest. However, (5) simultaneously the variables investment knowledge, risk perception, investment motivation and investment capital influence investment interest. Keywords : Investment Knowledge, Risk Perception, Investment Motivation, Investment Capital, Investment Interest